Preparation and performances of UV-cured methacrylated polyacrylic acid-based core-shell hybrid phase change materials - KAHRAMAN, MEMET VEZİR (WILEY, 2018)
In this study, UV-curable microencapsulated organic-inorganic hybrid phase change materials (micro-PCMs) were prepared; the micro-PCMs, which are based on a fatty alcohol core and a methacrylated polyacrylic acid (m-PAA) shell, were prepared by the sol-gel and UV-curing techniques. Polyacrylic acid (PAA) was reacted with glycidyl methacrylate to form methacrylated polyacrylic acid. The chemical structure of m-PAA was identified by Fourier transform infrared spectroscopy (ATR-FTIR).The differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) result showed that the micro-PCMs have the best phase change and thermal stability properties between 20 degrees C and 70 degrees C working temperature range. The melting latent heat enthalpy is measured between 100 and 140 J/g, and the freezing latent heat enthalpy is found between 90 and 130 J/g. An increase in microcapsule content resulted in an increase in the melting and freezing enthalpy of micro-PCMs for both the octedanol and the eicosanol core components. The encapsulation ratio and encapsulation efficiency are improved by increasing the core material content in the formulation. The decomposition temperatures of the organic-inorganic hybrid micro-PCMs increase by increasing the sol-gel content in the sample formulation. The obtained results indicated that these organic-inorganic hybrid micro-PCMs promise a great potential for the thermal energy storage application. POLYM. ENG. SCI., 58:2166-2174, 2018. (c) 2018 Society of Plastics Engineers
Keywords: THERMAL-ENERGY STORAGE; N-OCTADECANE; COMPOSITE; POLYMER; FABRICATION